The factor preventing the farmers in Miyazaki Prefecture to restart farming after 2010 Miyazaki foot-and-mouth disease outbreaks - Kadowaki, H.; Kayano, T.; Tobinaga, T.; Tsutsumi, A.; Watari, M.; Makita, K. (2012)
The purpose of this study is to reveal the factors by which they hesitate to restart farming activities suffering after Foot-and-mouth disease (FMD) outbreaks in Miyazaki 2010. Data were collected through interviews with 442 individuals in farming households in Miyazaki city and Shintomi and Kawaminami towns from August to November 2011 by Miyazaki Prefecture Mental Health and Welfare Center. In univariate analysis, associations between restarting of farming and agricultural, socio-economic, health and FMD related factors were examined. In multivariate analysis, generalized linear models were carried out. Response variable was selected as restarting of farming. As explanatory variables, the factors with p-value below 0.2 in the univariate analysis and the interaction terms with the correlation coefficients above 0.4 which might be logically associated with the factors were selected. Since there were several explanatory variables, two models: health associated and FMD associated models were developed. Health associated model was developed with factors related with health of farmers and their families for pig and cattle farms, respectively. FMD associated model was constructed with factors related with livestock and FMD control for vaccinated, infected and all farms, respectively. Stepwise model simplification was then employed. In the cattle farms, being elderly (OR 0.07, p=0.006) and K6 positive (OR 0.07, p=0.02) were preventive factors from restarting farming. On the contrary, being large scale farms (OR 1.01, p=0.009) and family-owned farms (OR 17.4, p=0.05) were encouraging factors. In pig farms, being large scale farms was an encouraging factor (OR 1.004, p=0.012). Among all farms, farmers who restarted were more dissatisfied with officially provided information on FMD (OR 0.6, p<0.001) while they were more satisfied with the current public support (OR1.3, p=0.03). Additionally, K6 positive was a preventive factor of restarting. Among farmers in infected farms, farmers which helped other farmers in culling tended to restart (OR 3.8, p=0.09). In conclusion, continuous mental health and psychosocial supports are warranted as the present study demonstrated that their suffering still persists. Furthermore, such psychosocial aspect should be a part of support in future animal infectious disease related disasters.